Knowledge Regarding Prevention of Mother to Child Transmission of HIV/AIDS among Antenatal Mothers in Nepal - Acharya, Radha; Acharya, Trishna; Devkota, Ramesh (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: Prevention of Mother to child Transmission (PMTCT) is a global intervention which aims at preventing mother to child transmission of Human Immunodeficiency Virus (HIV). The study aims to find out knowledge of pregnant women on Mother to child Transmission (MTCT) of HIV/AIDS (Acquired Immune Deficiency Syndrome). Materials & Methods: A cross-sectional study was carried out at Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal among the pregnant women who came to visit Antenatal Clinic. Data was collected using non-probability purposive sampling technique. Face to face interview was done and a structured questionnaire was developed for data collection. Data analysis and interpretation were done in SPSS and MS Excel. Results: The total number of respondents was 80 with a mean age of 27.4 years. 90% (n=72) respondents were found to be literate. 86.3% (n=69) were well aware of the knowledge on PMTCT. Majority of the respondents (40%) mentioned that radio, TV/Media were the main sources of information about HIV/AIDS. Out of 32.5% (26) who had heard about the window period, only 26.9% (n=7) gave the correct answer. 93.8% (n=75) were well known about the routes of transmission of HIV but only 10.1% (n=7) gave the correct answer about it. Further, 54% (n=43) respondents knew about the availability of drugs to reduce MTCT of HIV/AIDS. Conclusion: The level of awareness about PMTCT among antenatal mothers was satisfactory. However, knowledge was inadequate which imparts for the need of health education about MTCT of HIV/AIDS in every health facilities of Nepal.